FACE-TO-FACE LEARNING DURING THE PANDEMIC PERIOD COVID - 19 IN ENGLISH SUBJECT AT SMP NEGERI 5 AMARASI SATAP - Monas, Normalina; admin, admin (Publikasi dan UKI Press UKI Toraja., 2022)
The aim of this study to find out the effectiveness of face-to-face learning face-to-face learning during the pandemic covid-19 on social science subjects (ENGLISH) for class VII students at SMP Negeri 5 Amarasi Satap District , Makassar City . Method study quantitative could interpreted as method research based on the philosophy of positivism, the data is quantitative. Population and the sample of this study is the population of all students of class VII SMP Negeri 5 Amarasi Satap District , Makassar City which amount 46 people, and the sample that is whole student class VII SMP Negeri 5 Amarasi Satap District , totaling 46 people. Data is collected from value student report cards during face-to-face learning is limited, the data collected is analyzed use analysis technique statistics descriptive. Research result show that face-to-face learning Effective against social science learning (ENGLISH) students during the Covid-19 pandemic where the average student score was in the VII class namely with a total of 22 students with a percentage of 95.45% of students is at on category high.